Pengaruh Political Consumerism, Moral Intensity News Framing, Peer Pressure Terhadap Niat Boikot Melalui Social Media Response Sebagai Mediasi - Sartika, Fiona; Purnomo, Bintoro Bagus; Juniwati, Juniwati; Pebrianti, Wenny (CV. Era Digital Nusantara, 2025)
The phenomenon of boycotting multinational companies such as Nestlé has increased in response to moral, political, and human rights issues. This study analyzes the influence of moral intensity, news framing, peer pressure, and political consumerism on the intention to boycott Nestlé products in Indonesia, with social media response as a mediating variable. This quantitative study involved 412 Indonesian Muslim consumers who were active on social media and were aware of the Nestlé controversy regarding the Palestine-Israel issue, along with the appeal from the Indonesian Ulema Council (MUI) to support the boycott movement against products suspected of supporting Israeli aggression. Data were analyzed using PLS-SEM. The results showed that the four independent variables had a positive and significant effect on boycott intention. Moral news framing and peer pressure directly increased boycott intention, while political consumerism had the strongest influence, both directly and through the mediation of social media response. Consumers with high political awareness tend to voice their opinions on social media before taking real action in the form of a boycott.